Kejadian Stunting Pada Balita 12- 59 Bulan Di Puskesmas Kecamatan Cilincing Jakarta Utara: Description Of Stunting In Toddlers 12-59 Months At Puskesmas, Cilincing District, North Jakarta - Sasha Safira; Walliyana Kusumaningati (Poltekkes Kemenkes Palu, 2024)
Background. The toddler period is a critical stage in a child's development and growth. However, stunting remains a significant problem in Indonesia. The WHO has identified Indonesia as one of the five regions in Southeast Asia with a high prevalence of stunting. Aim. Therefore, this study aims to investigate the occurrence of stunting among children aged 12-59 months in the Community Health Center of Cilincing District, North Jakarta.Methods. The research method used is an analytic descriptive quantitative method with a cross-sectional approach. The population in this study were infants aged 0-59 months, totaling 26,033 toddlers in the working area of the Cilincing District Health Center, North Jakarta. The research sample consisted of 70 toddlers selected using a simple random sampling method. The data in this study were data on exclusive breastfeeding and data on a history of infectious diseases obtained from cohort data on stunting events in May, nutritional status, immunization, and interviews with respondents. Results. The results showed that the stunting rate in Cilincing District needed to be evenly distributed. The percentage of stunted toddlers who get exclusive breastfeeding is 83.56%, while those who do not get exclusive breastfeeding are 16.44%. The percentage of children under five who received immunization was 56.16%, while those who did not receive immunization were 43.84%. There were 15.07% of stunted toddlers with a history of infectious diseases, including coughs, colds, fever, diarrhea, and tuberculosis. Conclusion. Based on the study's results, there was no significant relationship between the incidence of stunting and exclusive breastfeeding, primary immunization, and a history of infectious diseases. Therefore, it is recommended that more attention be paid to other factors that can cause stunting